1999
DOI: 10.1038/9224
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the middle fusiform 'face area' increases with expertise in recognizing novel objects

Abstract: Part of the ventral temporal lobe is thought to be critical for face perception, but what determines this specialization remains unknown. We present evidence that expertise recruits the fusiform gyrus 'face area'. Functional magnetic resonance imaging (fMRI) was used to measure changes associated with increasing expertise in brain areas selected for their face preference. Acquisition of expertise with novel objects (greebles) led to increased activation in the right hemisphere face areas for matching of uprigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

74
835
11
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,084 publications
(926 citation statements)
references
References 33 publications
74
835
11
6
Order By: Relevance
“…Although the abstract paintings are as complex and interesting as the scenes and cover the same section of the visual field, they do not depict realistic three-dimensional environments and thus would be predicted by the spatial layout hypothesis to engage the PPA less strongly than the scenes, as we observed. The FFA, in line with previous findings [Gauthier et al, 1999;Tarr and Gauthier, 2000;Tong et al, 2000;Xu, 2005] while responding most strongly to faces, also responded more to other nonface stimuli than to the blank-screen baseline.…”
Section: Ffa and Ppa Activitysupporting
confidence: 90%
“…Although the abstract paintings are as complex and interesting as the scenes and cover the same section of the visual field, they do not depict realistic three-dimensional environments and thus would be predicted by the spatial layout hypothesis to engage the PPA less strongly than the scenes, as we observed. The FFA, in line with previous findings [Gauthier et al, 1999;Tarr and Gauthier, 2000;Tong et al, 2000;Xu, 2005] while responding most strongly to faces, also responded more to other nonface stimuli than to the blank-screen baseline.…”
Section: Ffa and Ppa Activitysupporting
confidence: 90%
“…3 Gauthier and colleagues have amassed a great deal of evidence for this hypothesis Gauthier, Anderson, Tarr, Skudlarski & Gore, 1997;Gauthier, Tarr, Moylan, Anderson & Gore, 1998;Gauthier, Tarr, Anderson, Skudlarski & Gore, 1999). Our experiments do not address the issue directly, but the nearest neighbor subordinate classification results for cups and cans (and, in fact, cup identification and can identification experiments we have not reported in detail) suggest that in many cases, subordinate classification may be biased toward low spatial frequency information.…”
Section: Subordinate Classification Accuracymentioning
confidence: 68%
“…This idea has been mostly put forward for face-selective regions, based on evidence that faces are processed more holistically than other types of object [105][106][107][108] . The hypothesis that the face-selective cortex is not actually selective for faces per se, but rather for the neural processing that is triggered by our extensive expertise with faces, has been tested with other object categories for which some individuals have expertise [109][110][111] -for example, cars and birds in car experts and ornithologists, respectively. However, recent evidence casts doubt on the idea that holistic processing occurs for any expert object category other than faces 112 , and all fMRI studies of expertise that investigated both the FFA and the LOC found that any increased responses to expert categories were larger in the LOC than in the FFA 112,113 .…”
Section: Basic Properties In the Ventral Visual Cortexmentioning
confidence: 99%